ANALISIS KINERJA PT PETROKIMIA GRESIK TAHUN 2011 MENUJU WORLD CLASS LEADER BERDASARKAN KRITERIA MALCOLM BALDRIGE 2011-2012 - Nugroho, Khristian Edi; Hayanto, Ririn Antika (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
Malcolm Baldrige criteria is a set of criteria and expectations to achieve performance excellence of aÂ company. PT Petrokimia Gresik â a fertilizer manufacturer that sells its products to both inside and outside theÂ country - has implemented the Malcolm Baldrige Criteria to improve its performance to be a World ClassÂ Leader. Out of the six other criteria, Leadership became part of a separate research and a research support toÂ the PT Petrokimia Gresik in connection with the relationship between Leadership and Innovation, performance,Â competitive advantage and sustainability (LIPCS). The empirical study and Managerial Implications in thisÂ study were simultaneously related to some reference books and journals. Further improvements to the companyÂ in general and specific refered to the increase in GDP and in the Global Competitive Index. Overall, the value ofÂ PT. Petrochemicals Gresik in 2011 based on the Malcolm Baldrige Criteria for 2011-2012 was 568 which wasÂ at Good Performance band. Nevertheless, there were three more bands to be passed to pursuit World ClassÂ Leader.